Olfactory ensheathing cells from the nasal mucosa and olfactory bulb have distinct membrane properties. Issue 5 (4th December 2019) - Smith, Katie E.; Whitcroft, Katherine; Law, Stuart; Andrews, Peter; Choi, David; Jagger, Daniel J.
Abstract: Transplantation of olfactory ensheathing cells (OECs) is a potential therapy for the regeneration of damaged neurons. While they maintain tissue homeostasis in the olfactory mucosa (OM) and olfactory bulb (OB), their regenerative properties also support the normal sense of smell by enabling continual turnover and axonal regrowth of olfactory sensory neurons (OSNs). However, the molecular physiology of OECs is not fully understood, especially that of OECs from the mucosa. Here, we carried out whole‐cell patch‐clamp recordings from individual OECs cultured from the OM and OB of the adult rat, and from the human OM. A subset of OECs from the rat OM cultured 1–3 days in vitro had large weakly rectifying K + currents, which were sensitive to Ba 2+ and desipramine, blockers of Kir4‐family channels. Kir4.1 immunofluorescence was detectable in cultured OM cells colabeled for the OEC marker S100, and in S100‐labeled cells found adjacent to OSN axons in mucosal sections. OECs cultured from rat OB had distinct properties though, displaying strongly rectifying inward currents at hyperpolarized membrane potentials and strongly rectifying outward currents at depolarized potentials. Kir4.1 immunofluorescence was not evident in OECs adjacent to axons of OSNs in the OB. A subset of human OECs cultured from the OM of adults had membrane properties comparable to those of the rat OM that is dominated by Ba 2+ ‐sensitive weak inwardly rectifying currents. The membrane properties of peripheral OECs are different to those of central OECs, suggesting they may play distinct roles during olfaction. Abstract : Olfactory ensheathing cells (OECs) are specialized glia, which wrap the axons of olfactory neurons that mediate the sense of smell. Their physiological roles during olfaction are largely unknown. Our electrophysiological characterization suggests that peripheral and central OECs are functionally distinct. Peripheral OECs have large weak inward rectifier currents, whereas central OECs have smaller strong inward rectifier currents and strong outward rectifier currents. These distinct sets of membrane properties may point to regional specializations in vivo .